PENGARUH KUALITAS LAYANAN SEKOLAH, KEPEMIMPINAN KEPALA SEKOLAH, DAN FASILITAS PEMBELAJARAN TERHADAP KEPUASAN PESERTA DIDIK DI SMKS MUHAMMADIYAH SE-KABUPATEN JEPARA - Choiruzaed; Yovitha Yuliejantiningsih; I. Made Sudana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Student satisfaction is very important in achieving educational goals. However, student satisfaction is not yet optimal. This is influenced by several factors: the quality of school services, the leadership of the school principal and learning facilities are important factors in determining the level of student satisfaction. The aims of this research are: (1) to determine the magnitude of the influence of school service quality on the satisfaction of Muhammadiyah Vocational School students throughout Jepara Regency; (2) to determine the magnitude of the influence of the principal's leadership on the satisfaction of SMKS Muhammadiyah students throughout Jepara Regency; (3) to determine the magnitude of the influence of learning facilities on the satisfaction of SMKS Muhammadiyah students throughout Jepara Regency; (4) to determine the magnitude of the influence of school service quality, school principal leadership, learning facilities on the satisfaction of Muhammadiyah Vocational School students throughout Jepara Regency. This research uses quantitative research with a non-experimental ex post facto type of research. The population in this study were 301 Muhammadiyah Vocational School students in Jepara Regency with a sample of 151 people using proportional random sampling techniques. The data collection technique uses a questionnaire method. The data analysis used is descriptive analysis, requirements testing and hypothesis testing using linear regression analysis and multiple linear regression with the SPSS version 20 program. The results of this research state that: (1) there is a significant influence of school service quality on student satisfaction with a large influence of 12% with the school service quality category being quite good; (2) there is a significant influence of the principal's leadership on student satisfaction with an influence of 6.4% and the principal's leadership category is quite good; (3) there is a significant influence of learning facilities on student satisfaction of 10.5% with the learning facilities category; (4) there is a simultaneous influence of service quality, principal leadership, learning facilities on student satisfaction with an influence of 17.8% with the level of satisfaction is quite good; (5) the total effective contribution is 17.73% with relative contribution (SR), SR X1 is 54%, SR X2 is 12% and SR X3 is 34%.